Faktor Yang Mempengaruhi Prokastinasi Akademik Siswa Dalam Pembelajaran Sejarah Kelas XI IPS Di SMA Negeri 1 Lembah Gumanti - Wirda Wati; Zafri Zafri (Jurusan Sejarah FIS UNP, 2021)
This research is motivated by students who are still delaying doing assignments or being late in collecting assignments in history learning. The purpose of this study is to reveal what are the most dominant factors that influence students' academic procrastination in learning history in class XI Social Sciences at SMA Negeri 1 Lembah Gumanti. This type of research is descriptive quantitative research with data collection techniques using a questionnaire or questionnaire. Based on the results of the study, it turns out that most students are influenced by the many factors that influence students' academic procrastination seen in internal and external factors. Overall the level of achievement with a percentage of 67% is in the high category. It can be concluded that the dominant factor that influences students' academic procrastination in learning history is the individual's physical condition which includes the student's health condition.